Flunitrazepam partitioning into natural membranes increases surface curvature and alters cellular morphology - Garcia, Daniel Asmed (2000)
In recent studies, we showed that flunitrazepam (FNTZ) and other benzodiazepines interact with artificial phospholipid membranes locating at the polar head group region, inducing a membrane expansion, reducing the molecular packing and reorganising molecular dipoles. In the present paper we investigated the possibility that those phenomena could be transduced into changes in the curvature of membranes from natural origin. Hence we studied the effect of FNTZ on cellular morphology using human erythrocyte as a natural assay system. Shape changes of erythrocytes were evaluated by light microscopy and expressed as a morphological index (MI). FNTZ induced echinocytosis in a time-dependent manner with MI values significantly higher than those of control (without drug) or DMSO (vehicle) samples. Lidocaine, a local anesthetic known to induce stomatocytosis by incorporating in the inner monolayer, counterbalanced the concentration-dependent FNTZ crenating effects. FNTZ induced protective effects, compared with control and DMSO, against time-dependent hemolysis. Hypotonic-induced hemolysis, was also lowered by FNTZ in a concentration-dependent manner. Both antihemolytic effects suggested a drug-induced membrane expansion allowing a greater increase in cell volume before lysis. In such a complex system like a cell, curvature changes triggered by drug partitioning towards the plasma membrane, might be an indirect effect exerted through modifications of ionic-gradients or by affecting cytoskeleton-membrane linkage. In spite of that, the curvature changes can be interpreted as a mechanism suitable to relieve the tension generated initially by drug incorporation into the bilayer and may be the resultant of the dynamic interactions of many molecular fluxes leading to satisfy the spontaneous membrane curvature. © 2000 Published by Elsevier Science Ireland Ltd.